Development of a Particulate Matter Sensor for Diesel Engine. (2015) - Grondin, D.; Breuil, P.; Viricelle, J.P.; Vernoux, P.
Abstract: A resistive soot sensor for diesel particulate filter (DPF) failure detection was developed in previous works. By measuring the conductance between two Pt electrodes, this sensor is able to detect a low leakage from the DPF but only provides soot mass information. In this study, we have characterized and determined the key parameters that influence the sensor response, i.e. the conductance with the aim to build a model that could provide soot number measurements. First results show a dependency of the sensor response with the soot mass concentration and the polarization level of the electrodes.